Analysis Critical Thinking Skills in Solving Statistical Problems in Terms of Self Concept - Agustina, Khusnul Hotimatus; Suryaningrum, Christine Wulandari; Firdaus, Hana Puspita Eka (IndoMath: Indonesia Mathematics Education, 2023)
This study aims to describe the critical thinking skills of class VIII B students at a private junior high school in Jember Regency. This type of research uses descriptive qualitative. Data collection techniques used questionnaires, written tests, and interviews. The subjects used by the researchers were class VIII B at a private junior high school in Jember Regency. Subject data obtained 3 self-concept classifications including high self-concept, moderate self-concept, and low self-concept. Based on the three self-concept classifications, students' critical thinking skills are then analyzed in 4 indicators, namely interpretation, analysis, evaluation, and inference. The results of the study show that students' critical thinking skills in each self-concept have different classifications. Students with high (positive) self-concept have high (critical) critical thinking skills, students with moderate self-concept have moderate (sufficient) critical thinking skills, while students with low (negative) self-concept have critical thinking skills with low (lack) in problem-solving.